2018
DOI: 10.1002/ange.201710424
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Oxidation by Polyoxometalate‐Supported Gold Nanoparticulate Catalysts: Activity, Stability, and Temperature‐ Dependent Activation Properties

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The pioneering work of the Haruta group on supported Au has triggered tremendous interest in low-temperature CO oxidation . Supported Au nanocluster catalysts have shown excellent activity below 0 °C. However, a cheaper alternative for this reaction is highly desirable. Some metal oxides, especially Co 3 O 4 , are also known to be active for CO oxidation at ambient temperature. CO oxidation below even −50 °C over Co 3 O 4 has been intensively studied, and varying activities (in terms of T 50 ) have been reported depending on physical properties and reaction conditions. ,,, The activity in Co 3 O 4 is significantly enhanced by doping with various metal substituents like Fe, Bi, In, etc., although these metals have hardly any role in the redox reaction itself. These few metal doped Co 3 O 4 catalysts have shown T 100 for CO oxidation at nearly −100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering work of the Haruta group on supported Au has triggered tremendous interest in low-temperature CO oxidation . Supported Au nanocluster catalysts have shown excellent activity below 0 °C. However, a cheaper alternative for this reaction is highly desirable. Some metal oxides, especially Co 3 O 4 , are also known to be active for CO oxidation at ambient temperature. CO oxidation below even −50 °C over Co 3 O 4 has been intensively studied, and varying activities (in terms of T 50 ) have been reported depending on physical properties and reaction conditions. ,,, The activity in Co 3 O 4 is significantly enhanced by doping with various metal substituents like Fe, Bi, In, etc., although these metals have hardly any role in the redox reaction itself. These few metal doped Co 3 O 4 catalysts have shown T 100 for CO oxidation at nearly −100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure and Figure S5, the absorption bands observed at ṽ = 2099 cm –1 on Au/TT-Ta 2 O 5 , ṽ = 2106 cm –1 on Au/P-Ta 2 O 5 , ṽ = 2101 cm –1 on Au/T-Ta 2 O 5 , and ṽ = 2093 cm –1 on Au/TiO 2 can be assigned to CO adsorbed on Au 0 . The bands at 2121 and 2133 cm –1 on Au/TT-Ta 2 O 5 and the band at 2120 cm –1 on Au/P-Ta 2 O 5 can be assigned to CO adsorbed on Au δ+ . ,, In the range of 2140 to 2200 cm –1 , the absorption bands of CO adsorbed on the Ta 2 O 5 sites and Au + were probably overlapped. It has been reported that the gold atoms at the perimeter interface showed Au δ+ and/or Au + characters. , The presence of Au + and/or Au δ+ suggested that the effective interaction between gold nanoparticles and the support was formed.…”
Section: Resultsmentioning
confidence: 92%
“…Au/Ta 2 O 5 was prepared by the SI method. , A solution of thiolate-protected gold colloids dissolved in 20 mL of toluene was added dropwise into a solution of Ta 2 O 5 dispersed in 10 mL of toluene. The mixture was stirred at room temperature for 1 h, and the solvent was evaporated under reduced pressure at 40 °C.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…There are several studies concerning the CO oxidation of different metals and supports, as reported in the review by Lui and Corma [2]. In fact, the catalytic oxidation of CO is the most effective process, as reported in the literature [3] [4] [5] [6] [7], using predominantly alumina-support and noble metals (Pt, Ru, Rh, and Pd) [8]- [13] and zeolite-supported platinum [13] [14] [15]. The met- [27].…”
Section: Introductionmentioning
confidence: 99%